Simulation of Power Factor Corrected AC-DC Boost Converter - Duranay, Zeynep Bala; Guldemir, Hanifi (Ieee, 2019)
A double loop control method, one for voltage control and the other for current control, for a power factor corrected ac-dc boost converter is studied in this paper. A classical PI controller is used for the load voltage regulation due to its slow dynamics with respect to fast changing current. A much faster hysteresis band current controller is used for the current control which has ease of physical implementation. The power factor corrected boost converter is simulated under different load conditions. The obtained results are presented. A good power factor is achieved.
11th International Conference on Electronics, Computers and Artificial Intelligence (ECAI) -- JUN 27-29, 2019 -- Pitesti, ROMANIA
Keywords: ac-dc convertor; boost convertor; power factor correction; unity power factor